The Effectiveness of a Community Psychiatric Rehabilitation Program Led by Laypeople in China: A Randomized Controlled Pilot Study - Chen, Ying; Lam, Chow S.; Deng, Hong; Yau, Eva; Ko, Kam ying (Frontiers in Psychiatry, 2021)
Background: Community psychiatric rehabilitation has proven effective in supporting individuals and their families in recovering from mental illness. The delivery of evidence-based community rehabilitation services, however, requires health care workers to possess a set of specially trained knowledge and skills. Most developing countries, including China, do not have specially trained mental health personnel. The purpose of this study was to test the feasibility and efficacy of a community psychiatric rehabilitation program delivered by laypeople. Method: We conducted a randomized controlled study. Patients at 2 sites in Chengdu, China, were randomly assigned to either the lay people delivered (LPD) community psychiatric rehabilitation group (N=49) or the drop-in center control group (N=45). The outcomes were changes in symptoms, social functioning and family functioning over 6 months, as measured by the Positive and Negative Syndrome Scale (PANSS), the Personal and Social Performance Scale (PSP), the Family Burden Scale of Disease (FBS), and the Family APGAR Index. Results: The number of sessions received over the 12-week period of treatment ranged from 20% to 100%, with a mean completion rate of 77.32% for all 12 sessions. Statistically significant interactions between group and time were found for the total PANSS (F2,94 = 12.51, p < .001) and both the Negative PANSS (F2,94 = 5.89, p < .01) and Positive PANSS (F2,94 = 6.65, p < .01) as well as the PSP (F2,94 = 3.34, p < .05), FBS (F2,94 = 5.10, p < .01), and Family ARGAR (F2,94 = 4.58, p <.01). The results showed that the experimental group outperformed their counterparts in symptom management, personal social functioning, family care burden and coherence. Conclusion: These results support the feasibility and efficacy of having laypeople deliver psychiatric rehabilitation services. A discussion and limitations of the study have been included.